Simulation Analysis of the Influence of Inclusion on Contact Fatigue Performance of Gear - Wenbo Zhang; Huaiju Liu; Caichao Zhu; Peitang Wei (Jixie chuandong)
Non-metallic inclusions in the gear have significant influence on the contact fatigue strength of gear. To improve the fatigue performance of the gear， it is essential to understand the mechanism of the influence of the non-metallic inclusions on the fatigue life of the gear. A finite element model of gear pair with inclusions is established， and the Brown-Miller multiaxial fatigue criterion is applied to predict the contact fatigue life. The influence of inclusion size， elasticity modulus， depth and arrangement of inclusions on contact fatigue performance of the gear is investigated. The results show that the size of inclusions increases the stress concentration area， with the increase of elastic modulus difference between inclusion and matrix， the harm of inclusion increases. The damage reaches its maximum when the inclusion located in the depth of about 0.49bH（contact half width depth）. The arrangement angle and spacing of two adjacent inclusions also affect the fatigue relief strength， with the decrease of the distance of the two adjacent inclusions， the stress concentration effect is more obvious， the harm will be greater.